Translation Strategies Used by Lingliana in Translating Taboo Words in Sylvia Day’s Bared to You - Lovihandrie, Hanhan; Mujiyanto, Januarius; Sutopo, Djoko (English Education Journal, 2018)
This study aimed at investigating the strategies which Indonesian translators use for translating of taboo words in Silvia Day’s novel entitled ‘Bared to You’, to analyze the implementation, and to analyze the equivalence achieved in the translation. In this study, a descriptive qualitative research is applied. The data were clasified using Batistella’s taboo categorisation and the translation strategies were further identified using the elaboration frameworks proposed by Davoodi, Robinson, and Brownlie. Then, Nida and Taber’s concept of equivalence was applied in determining the tendency of equivalence in the process of translating into target language. The results show that there are 555 taboo words found in the novel. Vulgarity dominates with 303 data, profanity 128 data, obscenity with 99, and last is ephitet with 25 data. The analysis on translation strategies shows that there are six strategies used by the translator in translating taboo words they are omission, euphemism, taboo for taboo, substitution, borrowing, and translation by more general word. Last, the analysis on the equivalence of translation shows that the translator tends to adopt more dynamic in translating taboo words into Indonesian.